Design and synthesis of five‐membered heterocyclic derivatives of istradefylline with comparable pharmacological activity. (30th May 2022) - Wang, Yiyun; Wang, Hongyi; Xu, Haojie; Zheng, Zhonghui; Meng, Zihui; Xu, Zhibin; Li, Jiarong; Xue, Min
Abstract: Parkinson's disease (PD) is a common degenerative disease of the central nervous system among the elderly. Istradefylline, an FDA‐approved adenosine A2A receptor antagonist (anti‐PD drug), has good efficacy. However, it has been reported that the double bond of istradefylline is easily converted into cis‐configuration when exposed to an indoor environment or direct light in a dilute solution. In order to find more stable adenosine A2A receptor antagonists with similar pharmacological efficacy to istradefylline, the compounds series I‐1 (12 compounds) was designed by maintaining the xanthine skeleton of istradefylline unchanged and replacing the trans‐double bond with thiazole or benzothiazole and other biologically active heterocyclic compounds. These compounds were synthesized via multi‐step experiment and successfully confirmed through different characterization techniques for their ability to inhibit cAMP formation in A2A AR overexpressing cells. The thiazole derivative of istradefylline (Compound I‐1‐11, I‐1‐12 ) exhibited significant activity (IC50  = 16.74 ± 4.11 μM, 10.36 ± 3.09 μM), as compared to istradefylline (IC50  = 5.05 ± 1.32 μM). In addition, the molecular docking of benzothiazole derivatives I‐1‐11 and thiazole derivatives I‐1‐12 with higher inhibition rate were carried out and compared with istradefylline. The molecular docking results showed that I‐1‐11 and I‐1‐12 anchored in the same site as that of XAC (3REY) with predicted affinity binding energy −6.63 kcal/mol and − 6.75 kcal/mol, respectively. Validation through dynamics simulation also showed stable interactions, with fluctuations <3 Å and MM/GBSA energy <−20 kcal/mol. Hence, this study could provide a basis for the rational design of adenosine A2A receptor antagonists with better potency. Abstract : A series of istradefylline derivatives were designed, synthesized, and evaluated for their biological activity in inhibited cAMP. The thiazole derivative of istradefylline (Compound I‐1‐12 ) exhibited significant activity (IC50 = 10.36 ± 3.09 μM), as compared to istradefylline (IC50 = 5.05 ± 1.32 μM).